Incomplete Information, Task Assignment, and Managerial Control Systems - Sridhar, Sri S.; Balachandran, Bala V. (Management Science, 1997)
A firm typically assigns multiple tasks it must perform to either internal employees or outside vendors. This paper demonstrates the need to integrate a task assignment decision with the design of a managerial control system as each affects the other. An internal employee is distinguished from an outside supplier on four different informational dimensions: (i) at the time of contracting, the outside supplier has less information about the task environment more often than the internal employee; (ii) the principal observes the employee's information set more frequently than that of the supplier; (iii) the principal can exercise a greater control over information flow to the internal employee than to the outside supplier; and (iv) the principal may share the details of the outside supplier's contract with the internal employee but not vice versa. Under each of these four distinguishing dimensions, the principal is shown to outsource the upstream task and assign the downstream task to the internal employee more often than vice versa. Further, under the last two dimensions of the firm's boundary, the principal can eliminate inefficiencies arising from the agents' contracting with incomplete information by assigning the downstream task to the employee and not providing predecision information to him while assigning the upstream task to the supplier.